Experiences of Opioid Use Disorder Patients Receiving Buprenorphine Through a Telehealth Program. Issue 3 (July 2021) - Moore, Dorothy James; Goyal, Deepika; Rodriguez, Lori
Abstract: Background: Opioid use disorder (OUD) continues to be a growing and major public health issue in the United States. In an effort to increase OUD treatment access, medication-assisted treatment with buprenorphine via telehealth is emerging as the leading treatment option. Objective: This study sought to describe the experiences of adults with OUD receiving medication-assisted treatment buprenorphine in a nurse-practitioner-facilitated telehealth program. Methods: Using a descriptive qualitative design, convenience sampling was used to recruit participants who were currently receiving OUD treatment in one telehealth program with locations in California and Michigan. Participants were invited to participate in the study via an email flyer sent to all clients of the telehealth program. Participants completed demographic data and took part in individual, semistructured interviews that were conducted online. Results: The study sample included 15 largely White, married, college-educated men ( n = 8, 53%) and women ( n = 7, 47%). Qualitative content analysis of interview data revealed three overall themes and associated subthemes: (a) improved access to care, (b) isolation, and (c) feeling normal on buprenorphine. Conclusion: Our findings support a nurse-practitioner-facilitated telehealth treatment program for OUD. However, in a program that offers patient-centered care that does not have a one-size-fits-all approach to service, goals of care must be reevaluated throughout treatment. Moreover, given the increased risk of patients feeling isolated with telehealth appointments and the lack of physical face-to-face interactions, healthcare providers should explore ways to engage patients in meaningful support resources and reduce stigma.